Compartimentos de C, P e N em solos sob pastagens degradadas na região sul do Estado do Espírito Santo - Silva, Amanda Gomes (2020)
The objective was to study the soil C, P and N compartments in soils under pasture with two levels of degradation in two seasons (winter and summer). It was assumed that the levels of the total compartments of these elements in soils under pastures used f